Congenital lingual melanotic macule: an underreported entity? - García-Montero, P.P.; Horcajada-Reales, C.; Hernández-Núñez, A.; Rojas-Mora, E.; Borbujo, J. (European Journal of Pediatric Dermatology, 2018)
none